ЭМОЦИЯ КАТЕГОРИЯСЫНЫҢ ФОНЕТИКАЛЫҚ СИСТЕМАДА СӘЎЛЕЛЕНИЎИ - Байрыева, М.Ж. (FAN va JAMIYAT, 2025)
In this article, we discussed the categorization of emotions, emotivers on the lexical-semantic front. From the lexical-semantic front, it is a set of content that illuminates a certain concept with a special order, composition and very different structure, and its structural elements are connected with paradigmatic relations.